Analisis Kesulitan Belajar Bahasa Arab Santriwati Tingkat Ibtida’ - Muzakkiyah, Nurul (Afkaruna: International Journal of Islamic Studies (AIJIS), 2024)
Abstract Arabic is one of the many languages in the world as the language of the Qur'an and Hadith which is the source of Islamic law so that without understanding it we will find it difficult to understand and understand the contents of the Qur'an and Hadith, therefore the language Arabic is a compulsory subject studied in Islamic educational institutions from Madrasah Ibtidaiyah to Islamic High School levels. In the process of learning Arabic, obstacles always exist, these obstacles cause many difficulties for female students in learning Arabic, both internal and external factors. This type of research is qualitative research. The results of the research show that firstly, there is a lack of motivation within the female students to learn Arabic, secondly, it is difficult for students to read and understand the meaning of each Arabic vocabulary word, thirdly, the teacher's delivery method is too monotonous, namely only using the lecture method and only using learning media. using books so that female students feel uninterested in learning Arabic more deeply.